TANGGUNG JAWAB PEMERINTAH DAERAH PADA PENEMPATAN DAN PERLINDUNGAN TENAGA KERJA INDONESIA MENUJU NEGARA KESEJAHTERAAN - Ferricha, Dian (Ahkam: Jurnal Hukum Islam, 2016)
Local government autonomy becomes an important moment to reflect the achievement of the nation development especially in immigrant worker protection. A good protection system will give a guarantee and certainty not only to the workers themselves but also to their families at home when they work overseas. The protection system should cover the pre-departure, the placement, and the repatriation. The Regulation Number 9 Year 2015 on Local Government open new hope for the local government to construct a good protection and placement system for the Indonesian immigrant workers since they are still at home. Kata kunci: Tanggungjawab, Pemerintahan Daerah, Tenaga Kerja Indonesia, Negara